AN ANALYSIS OF CODE SWITCHING IN THE HITAM PUTIH TALK SHOW - Siregar, Yuli Royanti; Jusmaya, Ance (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2020)
Code switching is a part of sociolinguistic phenomenon that often occurs in the community by using more than one language combination in one phrase or sentence. Code switching can be found anywhere. One of the common places where code switching can be found is in TV program. In the case, the aim of this study was to identify and analyze the types of code switching found in Hitam Putih talk show and the reasons for using the code switching. The theory used to analyze code switching in this study is related to tags, intrasentential, and intersentential is proposed by Stockwell (2002), while the theory used to analyze the reasons for using code switching is proposed by Hoffman (1991). The study uses qualitative research. The object of the study is code switching found in the Hitam Putih talk show. The results of this study showed that, out of 73 data that was analyzed, 19 of them contain switching tags. 48 data contain intrasentential switching, while the other 6 data contain intersentential switching. The writer also found a reason to use code switching in Hitam Putih talk show because of interjection, discussing a particular topic, being emphatic about something, repetition used for clarification, intention of clarifying the speech content for interlocutor, and expressing group identity.